2020
DOI: 10.3390/met10020162
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Improving Heat-Affected Zone Toughness of Steel Plate with Mg Deoxidation after High-Heat-Input Welding

Abstract: In the present study, the mechanism of improving HAZ toughness of steel plate with Mg deoxidation after the simulated welding with the heat input of 400 kJ/cm was investigated through in situ observation, characterization with SEM-EDS and TEM-EDS, and thermodynamic calculation. It was found that intragranular acicular ferrite (IAF) and polygonal ferrite (PF) contributed to the improvements of HAZ toughness in steels with Mg deoxidation. With the increase of Mg content in steel, the oxide in micron size inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…According to the SEM–EDS mapping results, the inclusion is identified to be MgO·Al 2 O 3 ·TiN·MnS inclusion with the diameter of about 2 μm. It is therefore demonstrated that the Mg containing complex inclusions with the size above 1 μm can effectively promote the nucleation and growth of intragranular ferrite, which is consistent with the results of our previous researches, [ 29,32,55,56 ] so as to prevent the generation of transverse corner cracks. In addition, the formed complex inclusions of the Mg containing oxides+(Ca, Mn)S, (Mg, Mn)S, or (Mg, Ca, Mn)S can also reduce the harmfulness of the extended MnS [ 57 ] to improve the transverse impact toughness of steel plate.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…According to the SEM–EDS mapping results, the inclusion is identified to be MgO·Al 2 O 3 ·TiN·MnS inclusion with the diameter of about 2 μm. It is therefore demonstrated that the Mg containing complex inclusions with the size above 1 μm can effectively promote the nucleation and growth of intragranular ferrite, which is consistent with the results of our previous researches, [ 29,32,55,56 ] so as to prevent the generation of transverse corner cracks. In addition, the formed complex inclusions of the Mg containing oxides+(Ca, Mn)S, (Mg, Mn)S, or (Mg, Ca, Mn)S can also reduce the harmfulness of the extended MnS [ 57 ] to improve the transverse impact toughness of steel plate.…”
Section: Resultssupporting
confidence: 90%
“…[ 27,28 ] With the development of injection metallurgy technology, Mg can be smoothly fed into molten steel by using Mg cored wire technology. At present, Mg treatment has been used in thick plate for the high heat input welding, [ 29–32 ] sulfur free‐cutting steel, [ 33,34 ] and ferritic stainless steel, [ 35,36 ] but the application of Mg treatment in peritectic steel is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of Si and Mn in the inclusions is caused by the absorption of Si and Mn in the base metal and welding wire during the growth of inclusions. Mn in the inclusions is also an important factor affecting AF nucleation [ 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…A range of ship plate steel products for high heat input welding were developed [43]. Furthermore, Yang's team from Shanghai University had long studied the effects of Mg treatment on inclusions in steel and the properties of welding HAZ, and they concluded that Mg treatment could refine inclusions and improve the toughness of HAZ [44][45][46]. Scholars from Northeastern University found that the low temperature impact toughness of HAZ were optimum when the Zr content in low carbon steel was 0.003%.…”
Section: Development Of Oxide Metallurgy Technologymentioning
confidence: 99%